The Scorch trials - Dashner, James 1972- (New York Delacorte Press, 2010)
After surviving horrific conditions in the Maze, Thomas is entrapped, along with nineteen other boys, in a scientific experiment designed to observe their responses and gather data believed to be essential for the survival of the human race
Sequel to: The maze runner
Sequel: The death cure
1 12
Keywords: Science fiction; Survival -- Fiction; Science fiction -- Juvenile